2021
DOI: 10.1016/j.prnil.2020.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Rebiopsy rate after transperineal or transrectal prostate biopsy

Abstract: Background In recent years, transperineal biopsies gained popularity for prostate cancer diagnosis; lower infective complications and improved sampling of the prostate are the main advantages of this technique. One question that remains unclear is whether an initial transperineal biopsy confers a lower risk for rebiopsy compared with the transrectal approach. Methods Six hundred seventy-one men were prospectively followed after an initial negative prostate biopsy for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The principal advantages over the TRs are reported as reduced bacterial contamination with the consequent reduction in UTIs and better access for the sampling of the anterior zone. Moreover, a recent paper by Marenco Jimenez et al 23 reported a significantly lower rebiopsy rate after TP-PB compared to TR ones.…”
Section: Discussionmentioning
confidence: 94%
“…The principal advantages over the TRs are reported as reduced bacterial contamination with the consequent reduction in UTIs and better access for the sampling of the anterior zone. Moreover, a recent paper by Marenco Jimenez et al 23 reported a significantly lower rebiopsy rate after TP-PB compared to TR ones.…”
Section: Discussionmentioning
confidence: 94%
“…At our institution, transperineal PBx was established after the conclusion of this study. There are data suggesting a higher tumor detection rate by targeted transperineal PBx and in patients undergoing repeated PBx [24]. However, tumor detection rates in systematic biopsies are comparable when performing transrectal or transperineal PBx [24].…”
Section: Discussionmentioning
confidence: 99%
“…There are data suggesting a higher tumor detection rate by targeted transperineal PBx and in patients undergoing repeated PBx [24]. However, tumor detection rates in systematic biopsies are comparable when performing transrectal or transperineal PBx [24]. Thus, the probability of missing both PCa and csPCa after new mpMRI revealed no high-grade PIRADS lesions appears to be minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative prophylactic use of antibiotics can better control the incidence of postoperative infection complications. In this study, diabetic patients suffered from postoperative infection complications due to preoperative prophylactic use of antibiotics.Study reported ( 30 ) that the re-biopsy rate of patients with traditional transrectal prostate biopsy was three times higher than that of transperineal prostate system biopsy (15.4% Vs 5.26%), and targeted biopsy could further reduce the re-biopsy rate. In this study, the re biopsy rates of patients in the 3D-TRUS group and TRUS group were 1.33% and 2.39%, slightly lower than the previous study results.…”
Section: Discussionmentioning
confidence: 99%